Development of central application and database module (CADM) of automated auxiliary weather system (AAWS) for Malaysian Meteorological Department (MetMalaysia) / Muhammad Zulfadli Sukarno - Sukarno, Muhammad Zulfadli (2016)
This thesis presents a research project on module development of an Automated Weather System in Meteorological Instruments Division (Bahagian Instrumentasi Meteorologi) for Malaysian Meteorology Department (Jabatan Meteorologi Malaysia). Due to data transmission retrieval practice used on previous Met Malaysia AWS, problem arise on efficiency on the retrieval of meteorological data. This motivates to the research of identifying new data transmission method to be used for next generation system. The system is Automated Auxiliary Weather System (Sistem Pencerapan Cuaca Permukaan Antomatik Anksiliari) and the module, Central Application and Database Module (CADM)developed based on the Software Development Life Cycle (SDLC). Four phases of Software Development Life Cycle (SDLC) is planning, requirement definition, design and development were used to produce next generation of system that manages Met Malaysia meteorological data. From these experiences, the researcher derived research in terms of project, people, technology, process and organization.